Identification of Volatile Compounds Involved in Host Location by Anthonomus grandis (Coleoptera: Curculionidae) - Magalhães, Diego M.; Borges, Miguel; Laumann, Raúl A.; Woodcock, Christine M.; Withall, David M.; Pickett, John A.; Birkett, Michael A.; Blassioli-Moraes, Maria C. (Frontiers in Ecology and Evolution, 2018)
Phytophagous insects rely on plant volatiles to locate suitable hosts upon which to feed or oviposit. The boll weevil, Anthonomus grandis, is the main pest on cotton crops in the Neotropical region and is attracted to host plant volatiles, especially herbivore-induced volatiles from reproductive cotton. Behavioral and electrophysiological responses of the boll weevil were evaluated aiming the identification of the compounds responsible for host location. We found that ten compounds elicited antennal responses from A. grandis, but only six were required to elicit a full behavioral response, namely: (R)-linalool, (E)-4,8-dimethyl-1,3,7-nonatriene (DMNT), methyl salicylate, (E)-(1R,9S)-caryophyllene, geranylacetone and (E-E)-4,8,12-trimethyl-1,3,7,11-tridecatetraene (TMTT). A synthetic blend comprising these six compounds was as attractive as the crude sample of cotton reproductive stage volatiles. These data are discussed in the context of insect host location and crop protection.